Forecasting Wheat Production in Punjab: An Appraisal (The Pakistan Development Review, 1976)
It is generally believed that Pakistan is not self-sufficient in wheat. Each year the government plans for wheat imports to fill the estimated shortage of wheat. Effective import policy can only be formulated on the basis of sound forecasting of the related variables. This note has a limited purposes of reviewing the existing forecasting techniques for wheat production. The broad conclusion that emerges from the review indicates a possibility of considerable scope for improvement in the current forecasting techniques.